PENGEMBANGAN BAHAN AJAR MATEMATIKA MATERI POLA BILANGAN BERSUMBER AL-QUR’AN DI KELAS VIII SMP/MTS - Suriyana, Nurma; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to develop of the Al-Qur’an-based mathematic teaching materials in number sequences topic for grade VIII students in junior high school. ADDIE model is used for develop this teaching materials. The quality of teaching material is reviewed based on three indicators: validity, effectiveness, and practicality. The instrument of data collection are validity questionnaire, post-test, and the practicality questionnaire. To know validity of teaching materials, subject matter expert and media expert filled the validity questionnaire. To know efektiveness of teaching materials, students are given post-test at the last of limited try-out. To know practicality of teaching materials, teacher and students filled the practicality questionnaire. The results of research covering the average score of validity questionnaire is 4,4; students passed through Minimum Completeness Criteria of 62.5%; and the average score of practicality questionnaire is 4,35. The conclusion of research is the mathematic teaching materials in number sequance topic for grade VIII students in junior high school have good quality by fulfilling the valid, effective, and practical to use. Keywords: Teaching Materials, Al-Qur'an Learning Resources, Number Sequences